A new indicator of leaf stomatal conductance based on thermal imaging for field grown cowpea. (2nd January 2020) - Iseki, Kohtaro; Olaleye, Olajumoke
ABSTRACT: Compared with a porometer, a thermal camera can be easily applied to large plant populations comprising a set of varieties, treatments, and replications, whereby, leaf temperature-based indicators are widely used to estimate stomatal conductance (gs ); however, a major difficulty in applying these indicators is their vulnerability to meteorological conditions. In this study, a new indicator of gs (GsI) was developed with a modified theoretical equation of gs that was highly simplified by means of several assumptions. GsI calculation uses leaf and air temperature, relative humidity, and solar radiation measurements. To validate and compare GsI values with other thermal indicators as leaf-air temperature difference and crop water stress index, glasshouse and field experiments were conducted. Leaf temperature of cowpea plants was measured using a low-cost thermal camera to ensure a cost-friendly method. GsI proved to be more stable than other indicators, relative to the measured gs, irrespective of solar radiation, air temperature, and relative humidity conditions. As no reference temperature is needed for the calculation of GsI, it easily applies to large plant populations, although the GsI is most accurate in the range from moderate to high gs values (approximately, >0.2 mol m −2  s −1 ). We used GsI to evaluate a cowpea germplasm collection consisting of 248 accessions, and elucidated that most accessions with higher GsI, which expected to have higher gs, are originated in West-Africa. As GsI is available regardless of varying meteorological conditions, it is a useful indicator of gs, especially in field studies involving multilocation and time-course evaluations. Abbreviations: Cp: specific heat of the air; CWSI: crop water stress index; DAS: days after sowing; DT: saturated vapor pressure at temperature T; ea: vapor pressure of the air; es: vapor pressure at leaf surface; G: heat flux to the ground; ga: boundary layer conductance; gs: stomatal conductance; gv: total conductance; RH: relative humidity; Rn: net radiation; Rs: short-wave radiation; S: heat flux to the leaf; Ta: air temperature; Tdry: dry reference temperature; Ts: leaf surface temperature; Twet: wet reference temperature; VPD: vapor pressure deficit; γ: psychrometric constant; λE: latent heat flux; ρ: air density. Graphical Abstract: